Habitat-specific morphological variation among threespine sticklebacks (Gasterosteus aculeatus) within a drainage basin. - Mike M Webster; Nicola Atton; Paul J B Hart; Ashley J W Ward (PLoS ONE, 2011)
Habitat-specific morphological variation, often corresponding to resource specialization, is well documented in freshwater fishes. In this study we used landmark based morphometric analyses to investigate morphological variation among threespine sticklebacks (Gasterosteus aculeatus L.) from four interconnected habitat types within a single lowland drainage basin in eastern England. These included the upper and lower reaches of the river, the estuary, a connected ditch network and a coastal salt marsh. We found significant habitat-specific differences in morphology, with three axes of variation describing differences in orbit diameter, body depth, caudal peduncle shape and pectoral fin positioning as well as variation in relative dorsal and pelvic spine size. Interestingly, the ditch system, an artificial and heavily managed habitat, is populated by sticklebacks with a characteristic morphology, suggesting that human management of habitats can in some circumstances lead to morphological variation among the animals that inhabit them. We discuss the mechanisms that conceivably underlie the observed morphological variation and the further work necessary to identify them. Finally, we consider the implications of habitat-specific body shape variation for the behavioural ecology of this ecologically generalist species.